PENGARUH METODE MENULIS BERANTAI (ESTAFET WRITING) TERHADAP KETERAMPILAN MENULIS DESKRIPSI DI KELAS IV SDN CARINGIN - Asmirul Diwansyah; Teguh Prasetyo; Sobrul Laeli (Fakultas Agama Islam dan Pendidikan Guru, 2022)
Writing skills are skills that are generally possessed by everyone. in managing thoughts, ideas, feelings and then applied or poured through written works that can be enjoyed by many people. The chain writing method is part of the active learning or learning by doing method, which is a learning activity that is not boring so that students become happy in receiving learning material. The purpose of this study is to determine whether there is an effect of the chain writing method on the students' writing description skills. This research was conducted in Class IV SDN Caringin 02 Bogor District. With a sample of 46 students. Which is divided into two groups, namely the experimental group and also the control group. The technique in this research is quantitative Quasi experiment method with Posttest Only Control Group Design. The data in this study were obtained through observation, test and documentation techniques by obtaining the results of the independent sample t test, the significance value of 0.010 ≤ 0.05, which shows that the relay writing method has an influence on the writing skills of the fourth grade students' description writing SDN 02 Caringin Bogor